Developing China’s Ecological Redline Policy using ecosystem services assessments for land use planning - Yang Bai (Nature Portfolio, 2018)
Ecosystem services, though a prominent ecological concept, have yet to be considered in major land use policy changes. Here, the authors demonstrate how the Ecological Redline Policy implemented in Shanghai utilized ecosystem services science and stakeholder engagement.